Analisis Struktur dan Nilai Moral dalam Cerita Rakyat Bawang Putih dan Bawang Merah: Perspektif Bahasa Indonesia dan Melayu - Melani Putri; Afdal Kusumanegara; Mira Anggaraini; Muhammad Akbar; Nadia Shalsa Nabila; Nesha Ramadhini (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
The folktale "Bawang Putih dan Bawang Merah" is one of the oral cultural heritages that is widespread in the Nusantara region, especially in the Indonesian and Malay language traditions. This study analyzes the narrative structure and moral values ​​contained in the story through a structural and hermeneutic approach. The analysis shows that this story has a distinctive structure with a pattern of family conflict, heroic journey, and moral resolution that reflects the traditional value system of the Malay-Indonesian community.